Application System for Checking Halal Product Status Using QR-Code Based on Android and Web - Hidayat Hidayat; Afrizal Imanullah (Jurnal Komputer Terapan, 2022)
This paper presents the design of an application system to quickly determine the halal product status circulating in Indonesian society by checking certification ID from LPPOM MUI. This is conducted to overcome the anxiety of the Muslim community in Indonesia on halal-labelled products that are sold in supermarkets and traditional markets. The system consists of two parts. Part one of the system uses PHP programming to record the halal certification of products and generate QR codes. Part two of the system uses an android application to scan the product's halal certification status from the QR codes. The information displayed on android is the product's name, the product manufacturer, the status of the product's halal certification, and other information. The results show that the application successfully scans the QR code and displays information on the halal certification status of the product. The smallest size of QR code version 1 that can be scanned is 0.6 x 06cm. The longest distance was 13cm.